Benefit of portal or superior mesenteric vein resection with adjuvant chemotherapy for patients with pancreatic head carcinoma. Issue 4 (6th August 2012) - Murakami, Yoshiaki; Uemura, Kenichiro; Sudo, Takeshi; Hashimoto, Yasushi; Nakashima, Akira; Kondo, Naru; Nakagawa, Naoya; Sueda, Taijiro
Abstract Background and Objectives The aim of this study was to evaluate the efficacy of portal or superior mesenteric vein (PV/SMV) resection for patients with pancreatic carcinoma who underwent pancreatoduodenectomy. Methods Medical records of 125 patients with pancreatic head carcinoma who underwent pancreatoduodenectomy were reviewed retrospectively. Sixty‐one patients underwent PV/SMV resection and 64 patients did not. Clinicopathological factors were compared between the two groups and the prognostic impact of PV/SMV resection was evaluated using univariate and multivariate survival analysis. Results The frequency of mortality and morbidity did not differ between the two groups. Univariate analysis revealed that a significant difference in overall survival was found between patients who did and did not undergo PV/SMV resection (P = 0.046) as well as between patients with and without pathological PV/SMV invasion (P = 0.012). However, PV/SMV resection and pathological PV/SMV invasion were not independent prognostic factors by multivariate survival analysis. Among patients with PV/SMV resection, the use of adjuvant chemotherapy was the only independent prognostic factor of overall survival (P = 0.003). Conclusions Resection of the PV/SMV with adjuvant chemotherapy may provide an acceptable survival benefit to patients with pancreatic head carcinoma, which involves the PV/SMV without additional mortality and morbidity. J. Surg. Oncol. 2013;107:414–421. © 2012 Wiley Periodicals, Inc.